CD8 T Cell Response and Evolutionary Pressure to HIV-1 Cryptic Epitopes Derived from Antisense Transcription - Bansal, Anju; Carlson, Jonathan M.; Yan, Jiyu; Akinsiku, Olusimidele T.; Schaefer, Malinda; Sabbaj, Steffanie; Bet, Anne; Levy, David N.; Heath, Sonya; Tang, Jianming; Kaslow, Richard A; Walker, Bruce D.; et al. (The Journal of Experimental Medicine, 2010)
HIV immune escape in alternative reading frame From time to time, the protein traslational machinery gets messed up, slipping a bit so that translation happens out of frame. The result is of course disfunctional protein fragments, which quickly get chewed up by the proteosome. We wondered if some of these were be presented as epitopes. If so, then HIV would of course escape (it always does!), and we would thus be able to find them by looking for HLA-mediated escape in non-primary reading frames. In back to back papers in the Journal of Experimental Medicine, we showed that this is indeed what's happening. In collaboration with Christian Brander's group, the first paper did a deep dive into one epitope, showing that the "cryptic epitope" was expressed was by translation at an alternative start size that would normally encode a lysine. In an independent paper with Paul Goepfert's group, we showed that cryptic epitopes are frequently targeted–especially in antisense reading frames (ie, the genome was transcribed "Backwards" on the 3' strand). Another great example of using HIV adaptation as a starting point for learning something fundamentally knew about how our immune systems interact with viruses. Will be interesting to see if these lead to new vaccine targets. These papers were picked up by several news aggregators and bloggers. Abstract Retroviruses pack multiple genes into relatively small genomes by encoding several genes in the same genomic region with overlapping reading frames. Both sense and antisense HIV-1 transcripts contain open reading frames for known functional proteins as well as numerous alternative reading frames (ARFs). At least some ARFs have the potential to encode proteins of unknown function, and their antigenic properties can be considered as cryptic epitopes (CEs). To examine the extent of active immune response to virally encoded CEs, we analyzed human leukocyte antigen class I–associated polymorphisms in HIV-1 gag, pol, and nef genes from a large cohort of South Africans with chronic infection. In all, 391 CEs and 168 conventional epitopes were predicted, with the majority (307; 79%) of CEs derived from antisense transcripts. In further evaluation of CD8 T cell responses to a subset of the predicted CEs in patients with primary or chronic infection, both sense- and antisense-encoded CEs were immunogenic at both stages of infection. In addition, CEs often mutated during the first year of infection, which was consistent with immune selection for escape variants. These findings indicate that the HIV-1 genome might encode and deploy a large potential repertoire of unconventional epitopes to enhance vaccine-induced antiviral immunity.